2006
DOI: 10.1101/gr.4237406
|View full text |Cite
|
Sign up to set email alerts
|

Establishing glucose- and ABA-regulated transcription networks in Arabidopsis by microarray analysis and promoter classification using a Relevance Vector Machine

Abstract: Establishing transcriptional regulatory networks by analysis of gene expression data and promoter sequences shows great promise. We developed a novel promoter classification method using a Relevance Vector Machine (RVM) and Bayesian statistical principles to identify discriminatory features in the promoter sequences of genes that can correctly classify transcriptional responses. The method was applied to microarray data obtained from Arabidopsis seedlings treated with glucose or abscisic acid (ABA). Of those g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
253
2
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 234 publications
(273 citation statements)
references
References 96 publications
(106 reference statements)
11
253
2
7
Order By: Relevance
“…Previous studies have shown that this gene is induced under conditions of sugar feeding and during sugar-induced senescence (Gonzali et al, 2006;Li et al, 2006;Pourtau et al, 2006). In vitro evidence shows that this gene product is a functional sugar phosphate/phosphate translocator, with activity for triose-and hexose-Ps (Knappe et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that this gene is induced under conditions of sugar feeding and during sugar-induced senescence (Gonzali et al, 2006;Li et al, 2006;Pourtau et al, 2006). In vitro evidence shows that this gene product is a functional sugar phosphate/phosphate translocator, with activity for triose-and hexose-Ps (Knappe et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It functions in vitro to transport both Glc-6-P and triose-P in exchange for phosphate (Knappe et al, 2003). Reported expression levels have typically been low, though it has been identified as being up-regulated in response to sugar feeding (Gonzali et al, 2006;Li et al, 2006) and during leaf senescence (Pourtau et al, 2006). In the Col-0 ecotype, which is unable to acclimate dynamically but which expresses the GPT2 gene, it was reported that gpt22 mutants grow normally (Niewiadomski et al, 2005).…”
Section: Dynamic Acclimation Increases Fitness Under Naturally Variabmentioning
confidence: 99%
“…1,A and B). TANG2 was originally found to be one of thousands of genes whose expression was rapidly altered in response to Glc (Li et al, 2006). OTP439 was identified through a Genevestigator (https://www.…”
Section: Phenotypes Of the Tang2 And Otp439 Mutantsmentioning
confidence: 99%
“…Like nitrate, exogenous Suc and Glc influence the expression of many genes involved in metabolism and growth, including amino acid biosynthetic genes, ribosome synthesis genes, and hormone-regulated genes (Li et al, 2006). Network analyses (Gutiérrez et al, 2007) identified interdependent transcriptional responses to Glc and nitrate, including genes for auxin responses and signaling, transcription factors, and signal transduction proteins.…”
mentioning
confidence: 99%
“…Expression of genes encoding the high-affinity nitrate transporters NRT2.1 and NRT2.2 is repressed by high nitrate levels and activated in low-nitrate conditions to scavenge available soil nitrate (Li et al, 2006;Gojon et al, 2011;Xu et al, 2012;Wang et al, 2012b). NRT2.4 encodes an N starvationinduced high-affinity transporter (Kiba et al, 2012).…”
mentioning
confidence: 99%